2020
DOI: 10.1101/2020.02.11.944462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM Structure of the 2019-nCoV Spike in the Prefusion Conformation

Abstract: 1The outbreak of a novel betacoronavirus (2019-nCov) represents a pandemic threat that has been 2 declared a public health emergency of international concern. The CoV spike (S) glycoprotein is a 3 key target for urgently needed vaccines, therapeutic antibodies, and diagnostics. To facilitate 4 medical countermeasure (MCM) development we determined a 3.5 Å-resolution cryo-EM 5 structure of the 2019-nCoV S trimer in the prefusion conformation. The predominant state of the 6 trimer has one of the three receptor-b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

68
1,910
3
22

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,351 publications
(2,021 citation statements)
references
References 38 publications
68
1,910
3
22
Order By: Relevance
“…Five out of the six critical amino acid (AA) residues in RBD were different between SARS-CoV-2 and SARS-CoV ( Fig. 1B), and a 3D structural analysis indicated that the spike of SARS-CoV-2 has a higher binding affinity to ACE2 than SARS-CoV [23]. Intriguingly, these same six critical AAs are identical between GD Pangolin-CoV and SARS-CoV-2 [16].…”
Section: Molecular Phylogeny and Divergence Between Sars-cov-2 And Rementioning
confidence: 97%
See 1 more Smart Citation
“…Five out of the six critical amino acid (AA) residues in RBD were different between SARS-CoV-2 and SARS-CoV ( Fig. 1B), and a 3D structural analysis indicated that the spike of SARS-CoV-2 has a higher binding affinity to ACE2 than SARS-CoV [23]. Intriguingly, these same six critical AAs are identical between GD Pangolin-CoV and SARS-CoV-2 [16].…”
Section: Molecular Phylogeny and Divergence Between Sars-cov-2 And Rementioning
confidence: 97%
“…Both SARS-CoV and SARS-CoV-2 bind to ACE2 through the RBD of spike protein in order to initiate membrane fusion and enter human cells [1,2,[22][23][24][25][26]. Five out of the six critical amino acid (AA) residues in RBD were different between SARS-CoV-2 and SARS-CoV ( Fig.…”
Section: Molecular Phylogeny and Divergence Between Sars-cov-2 And Rementioning
confidence: 99%
“…S residues 313-532 were clearly interpretable from the electron density map, with a dual conformation of a loop containing residues 484 to 487 clearly visible in the electron density map (Figure 1). Structure comparison of the unliganded RBD structure presented here, with the stabilized prefusion SARS-CoV-2 Spike (S-2P) molecule structure determined by Cryo-EM (PDB ID: 6VSB) (Wrapp et al, 2020) shows high structural similarity, with an RMSD of 0.68, 0.68, and 0.71 for each of the spike protomers. In the structure of the S-2P molecule (S-2P) (Wrapp et al, 2020) 25, 29 or 49 amino acids (aa) within each protomer RBD are not modeled, including 40% of the ACE-2 receptor binding site as measured by buried surface area (BSA) (Yan et al, 2020b).…”
Section: High Resolution Structure Of the Sars-cov-2 Rbdmentioning
confidence: 96%
“…Recently, the molecular structure of recombinant full-length SARS-CoV-2 Spike protein was solved in a stabilized pre-fusion state, by single particle cryo-Electron Microscopy (cryo-EM), at a resolution of 3.8 Å (Wrapp et al, 2020). Despite the comprehensive structural characterization of the spike protein as a whole, movement of the RBD between "up" and "down" conformational states prevented complete modeling of the RBD domains.…”
Section: Introductionmentioning
confidence: 99%
“…WHO formally designated the name of the novel coronavirus as COVID-19 on February 11th, 2020. The virus responsible for COVID-19 are deem as highly contagious infectious comparing with SARS, which caused cluster pneumonia cases emergence during the year 2002 and 2003 [2]. According to the Situation Report -28 released by the WHO, there are 71429 confirmed globally, among which there are 70635 confirmed in China [3].…”
Section: Introductionmentioning
confidence: 99%